Managing for performance: Measurement and monitoring of contracts in the transit industry. Issue 2 (1st March 2016) - Smirnova, Olga; Yusuf, Juita-Elena (Wie); Leland, Suzanne
Abstract : Public agencies contract out to pursue a variety of goals. But, these goals cannot be realized if the performance of contractors is not assessed and monitored. This study examines the state of performance measurement and contract monitoring in the U.S. transit agencies. We focus on three research questions: (1) What monitoring capacity exists within transit agencies? (2) What monitoring methods are used by transit agencies? (3) What performance measures are tracked by transit agencies? We find monitoring units are common in a third of agencies in the study. Service and customer complaints are the most common performance measures, while penalties and liquidated damages are the most frequent form of penalties. Finally, we find that transit agencies utilize a variety of output and outcome measures to monitor contractors.